Rare and first case report of a diffused cutaneous leishmaniasis from Uttar Pradesh state, India - Hasmatullah Khan; Vindu Prakash Singh; Gaurav Raj Dwivedi; Ayush Mishra; Nalini Mishra (Journal of Vector Borne Diseases)
Kala-azar is common in Bihar state of India and some bordering areas of Uttar Pradesh but cutaneous, diffused and mucocutaneous leishmaniasis is not yet reported in areas of Uttar Pradesh, India. A rare case of diffuse cutaneous leishmaniasis was reported from a resident of Karaundi village of Deoria district of Uttar Pradesh with no history of travel to endemic areas of this disease. The present case report raises alarm for the presence of this disease in this region and raises the question of whether the vector is present with compatibility to carry this parasite which has not been reported till present. Future molecular diagnosis and vector studies are required for confirmation and to prevent future outbreaks.